Evaluasi Kinerja Pengelolaan Proyek Strategis Nasional Indonesia Sampai dengan 31 Desember 2023 - Hamdani, Hamdani (Universitas Batanghari Jambi, 2025)
The purpose of this study is to evaluate the accountability and transparency of the performance of National Strategic Project (PSN) management. This study uses a qualitative method with a review of literature and available data. The evaluation of PSN performance is based on six criteria: budget realization performance, PSN selection, project start schedule, project completion schedule, transparency and accountability, and investment efficiency. The results show that all six performance aspects are not optimal, especially in the planning, licensing, and completion processes. With the target of completing the PSN before the end of President Joko Widodo's term, this study is expected to contribute to accelerating project completion.